Sociodemographic and clinical characteristics of elderly patients in alcohol dependence treatment - Cengisiz, Cengiz; Bölükbaşı, Selman (Journal of Dependence, 2025)
Objective: This study aimed to examine the prevalence, sociodemographic characteristics, and clinical features of alcohol use disorder (AUD) in individuals aged 60 years and older.Method: A retrospective cohort analysis was conducted on 3892 patients aged 60 and over who were diagnosed with AUD and admitted to the Addiction Counseling Outpatient Clinic of Manisa Mental Health and Diseases Hospital between 2019 and 2023. Sociodemographic data, comorbidities, and treatment approaches were evaluated.Results: Among the participants, 93.6% were male and 6.4% were female. The prevalence of AUD was higher among males; however, a significant increase in alcohol consumption among females was observed during the pandemic period. The mean age was 64.6±4.4 years, and 89% of the patients received outpatient treatment. Patients from metropolitan areas, such as İzmir, showed higher rates of inpatient treatment. The most common physical comorbidities were hypertension (51.6%) and malnutrition (31.4%), while the most frequent psychiatric comorbidities were depression (19.8%) and dementia/cognitive impairment (17.3%).Conclusion: In geriatric individuals, AUD frequently coexists with significant physical and psychosocial comorbidities. These findings emphasize the importance of early diagnosis, interdisciplinary approaches, and comprehensive psychosocial support services. Future studies should aim to raise awareness of AUD among the elderly and develop holistic intervention strategies.
Keywords: Elderly; alcohol-related disorders; geriatric psychiatry; substance-related disorders